Kepemimpinan Kiai Pesantren: Studi terhadap Pondok Pesantren di Kota Jambi - Anwar US., Kasful (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2010)
This article discusses about leadership of Islamic leader (kiai) in Islamic boarding school (pesantren) in Jambi. It focusses on the kiai selection system in Islamic boarding school, leadership model that is developed by kiai, its effectiveness, and kiai roles in the community. According to the research conducted in three Islamic boarding schools, it was found that leadership patterns in Islamic schools in Jambi are different. The selections are based on the discussion, descent, and government appointment. However, in general, leadership model develops in Islamic boarding schools in Jambi is collective-pasive, in which the institutions under their foundation, but in practice, they follow individual leardership. As a result, kiai leadership is not effective yet because management is not implemented optimally.